2003
DOI: 10.1007/s00261-003-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

MR staging of primary colorectal carcinoma: comparison with surgical and histopathologic findings

Abstract: MR imaging using currently available techniques can effectively image local tumor extent and distant metastases in patients with colorectal carcinoma. Especially for colon cancer, incomplete depiction of nodal metastases in normal-size lymph nodes remains a limitation of cross-sectional imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…With a larger population, MRI‐EMVI score might become significant in multivariable analysis, in keeping with histological studies identifying EMVI as an independent prognostic feature10, 13. The present finding that MRI‐predicted lymph node status did not correlate with outcome even in univariable analysis emphasizes the well documented difficulties of nodal staging with MRI22, 23.…”
Section: Discussionsupporting
confidence: 79%
“…With a larger population, MRI‐EMVI score might become significant in multivariable analysis, in keeping with histological studies identifying EMVI as an independent prognostic feature10, 13. The present finding that MRI‐predicted lymph node status did not correlate with outcome even in univariable analysis emphasizes the well documented difficulties of nodal staging with MRI22, 23.…”
Section: Discussionsupporting
confidence: 79%
“…Another smaller study has also demonstrated good correspondence between histopathology and MRI for measurement of EMD (Fig. 13) [73].
Fig.
…”
Section: Extramural Tumour Growth or Depthmentioning
confidence: 83%
“…13 The accuracy of lymph node metastasis by CT scan has been reported at 79.2%, with a sensitivity of 88.5%; 15 however, more recent studies using MRI have emerged, which show superior predictability to TRUS or CT, with a diagnostic accuracy of nodal metastasis of 98% and sensitivity of 93%. 16 The report of the National Veterans Administration Randomized Study 17 stated that patients with rectal cancer who had been irradiated preoperatively had an earlier Duke stage than controls. However, it is unclear whether this was a result of the true eradication of cancer in lymph nodes or attributable to failure of accurate assessment of regressed lymph nodes after radiotherapy.…”
Section: Discussionmentioning
confidence: 98%